86.6k views
5 votes
2b^2x^2+3a^2y^2=a^2b^2 for b^2

1 Answer

2 votes

Answer:


{b}^(2) = \frac{3 {a}^(2) {y}^(2) }{ {a}^(2) - 2 {x}^(2) }

Explanation:

We want to solve for b² in


2 {b}^(2) {x}^(2) + 3 {a}^(2) {y}^(2) = {a}^(2) {b}^(2)

Combine terms containing b²


3 {a}^(2) {y}^(2) = {a}^(2) {b}^(2) - 2 {b}^(2) {x}^(2)

Factor b² to get:


3 {a}^(2) {y}^(2) = ({a}^(2) - 2 {x}^(2)) {b}^(2)

Divide by a² -2b²


{b}^(2) = \frac{3 {a}^(2) {y}^(2) }{ {a}^(2) - 2 {x}^(2) }

User Sander Smith
by
5.1k points